Family Cohesion and Stress Consequences Among Chinese College Students During COVID-19 Pandemic: A Moderated Mediation Model - Zeng, Yadi; Ye, Baojuan; Zhang, Yanzhen; Yang, Qiang (Frontiers in Public Health, 2021)
Family plays a pivotal role in individuals’ mental health. During the COVID-19 epidemic, people were being quarantined at home to prevent the further spread of the virus. Therefore, the influence of family on individuals is more significant than usual. It is reasonable to assume that family cohesion can effectively alleviate the stress consequences during the COVID-19 epidemic. In the present study, a moderated mediation model was constructed to examine the mechanisms underlying the association between family cohesion and stress consequences among Chinese college students. A large sample of Chinese college students (N = 1,254, Mage=19.85, SDage=1.29) participated in the study. Results indicated that family cohesion was negatively related to stress consequences. Fear of COVID-19 partially mediated the link between family cohesion and stress consequences. Excessive affective empathy reported by participants served to aggravate the relation between fear of COVID-19 and stress consequences. The study helps us understand how internal and external factors affect individual mental health that provides meaningful implications for promoting mental health.